2016
DOI: 10.1002/jssc.201501207
|View full text |Cite
|
Sign up to set email alerts
|

Agarose‐ and alginate‐based biopolymers for sample preparation: Excellent green extraction tools for this century

Abstract: Recently, there has been considerable interest in the use of miniaturized sample preparation techniques before the chromatographic monitoring of the analytes in unknown complex compositions. The use of biopolymer-based sorbents in solid-phase microextraction techniques has achieved a good reputation. A great variety of polysaccharides can be extracted from marine plants or microorganisms. Seaweeds are the major sources of polysaccharides such as alginate, agar, agarose, as well as carrageenans. Agarose and alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Due to the complex alterations associated with IR injury, it has become difficult to identify a novel pharmacological drug with a protective effect. Previous studies preferentially developed therapeutics for IR injury based on the advantages of traditional Chinese medicine (TCM) ( 15 , 16 ). Seaweed is one of the most abundant sources of polysaccharides used in TCM, with alginate, agar, fucoidan, agarose and carrageenan all present ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complex alterations associated with IR injury, it has become difficult to identify a novel pharmacological drug with a protective effect. Previous studies preferentially developed therapeutics for IR injury based on the advantages of traditional Chinese medicine (TCM) ( 15 , 16 ). Seaweed is one of the most abundant sources of polysaccharides used in TCM, with alginate, agar, fucoidan, agarose and carrageenan all present ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies preferentially developed therapeutics for IR injury based on the advantages of traditional Chinese medicine (TCM) ( 15 , 16 ). Seaweed is one of the most abundant sources of polysaccharides used in TCM, with alginate, agar, fucoidan, agarose and carrageenan all present ( 16 ). A previous study demonstrated that M. charantia polysaccharide (MCP) could be a promising neuroprotective ingredient of M. charantia and its mechanisms could be at least in part attributed to its antioxidant activities and its inhibition of JNK3 signaling cascades during cerebral ischemia/reperfusion injury in a rat model ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Before using any analytical technique, sample preparation is carried out to get rid of many other constituents [ 22 ]. Besides, the sample preparation is used to concentrate the analytes of interest as, sometimes, the analytes are at low concentrations and beyond the scope of the detection of the analytical instrument [ 23 ]. Various sample preparation methods are used for the analysis of phenols and these include liquid-liquid extraction (LLE), solid-phase extraction (SPE), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Alginate is a biopolymer extracted from brown algae and consists of edible polysaccharides with homopolymeric blocks of 1-4 linked d-mannuronate and L-guluronate [24]. Alginate has been explored as supporting material by encapsulating with activated carbon [25], carbon [17], synthetic polymer [26] and maghemite nanoparticles [27] to form as adsorbents for heavy metals, dyes and other pollutants [1,28]. To the best of our knowledge, there are only few investigations focused on comparison adsorption studies towards dyes removal by carbonaceous materials with alginate.…”
Section: Introductionmentioning
confidence: 99%